Desarrollo e implementación de un software educativo como apoyo didáctico para la asignatura de ciencias naturales, dirigido a los estudiantes de cuarto año de educación básica, de la escuela “Eliseo Álvarez”, de la ciudad de Loja, período lectivo 2013-2014. - Morocho Abril, Luis Fabián (2015)
This study was conducted in order to develop and implement an educational software and instructional support for the subject of Natural Sciences, aimed at students in the fourth year of primary education tax school “Eliseo Álvarez” in the city of Loja, school year 2013-2014. The main objective is stated: "It Develop and implement an educational software and instructional support for the subject of natural sciences, aimed at students in the fourth year of primary education Fiscal School girls “Eliseo Álvarez," the city of Loja, 2013-2014 school year, "and the following specific objectives were set: Determine the level of knowledge among teachers regarding the design of educational Software for the subject of Natural Sciences for the fourth year of primary education. Develop an educational software as instructional support for the subject of science aimed at students in the fourth year of primary education, educational software Implement proposed for the subject of science aimed at students in the fourth year of primary education and develop a manual user for the use of educational software proposed for the subject of Natural Sciences for girls attending fourth year of primary education. The methodology involved the use of methods such as methods: scientific, inductive, deductive, analytical, and application of the following research techniques: direct observation, interviews and observation guide. From observation guide girls fourth year of basic education, it is evidenced that 100% of the classes of the subject of Natural Sciences are not dynamic; 50% of the students recall the knowledge imparted by the teacher and 50% almost never remember; 50% of classes are participatory and 50% are seldom participatory, values that determine that girls are more difficult to learn and teachers to teach.